Barriers and facilitators to implementing a multilevel, multicomponent intervention promoting colorectal cancer screening in health centers: a qualitative study of key informant perspectives - V. M. Telles; S. Rodriguez; M. Torres; J. Schneider; J. Haughton; M. Maldonado; E. Arredondo (BMC, 2024)
Abstract Background Colorectal cancer (CRC) continues to be a major cause of death in the U.S. despite the availability of effective screening tools. U.S. Latinos have lower rates of CRC screening and higher rates of death due to colorectal disease compared to non-Hispanic whites. Federally Qualified Health Centers (FQHCs) serve medically underserved populations, including many Latino patients. Given the low CRC screening rates, identifying culturally sensitive and cost-effective methods of promoting screening is a priority for many FQHCs. Methods We interviewed FQHC leaders and providers using the Consolidated Framework for Implementation Research (CFIR) to identify barriers and facilitators to implementation of a multilevel, multicomponent (ML-MC) CRC screening intervention (i.e., promotor navigation and group-based education) in FQHCs. A rapid qualitative analysis approach was used to identify themes organized according to the following CFIR constructs: intervention characteristics, outer and inner settings, and characteristics of the individual. Results We completed interviews with 13 healthcare professionals in leadership positions at six FQHCs. The participating FQHCs perceived the ML-MC screening CRC program as feasible and expressed interest in implementing the program at their sites. Facilitators included financial incentives for increasing screening rates, the need for patient education programming, and involving promotores to support the work of clinical teams. Barriers included concerns about available resources to implement new programs, lack of federal reimbursement for health education, competing priorities of other health concerns, and the need for more resources for confirmatory screening and treatment following a positive screen. Conclusions FQHCs provide essential primary care to millions of underserved patients in the U.S. and have the ability and motivation to provide screenings for colorectal cancer. Partnering with an academic institution to deliver a group-based, promotor-led CRC screening intervention for patients not up to date with screening could help increase screening rates. By identifying the specific barriers and facilitators to implementing CRC intervention, findings suggest that group-based, promotor-led interventions are a promising approach.